Turanism as a political myth in the context of the Hungarian politics of memory - Hornok, Rita (Society Register, 2025)
The article aims to analyze how the Hungarian myths of (Central Asian) origin and other Turanist narratives are instrumentalized by the Hungarian government for political purposes. The research focuses on Hungarian political discourses of the Fidesz government between 2010 and 2022, which reflect the use of Turanist myths as part of a political strategy. The article’s central question is how and for what purposes national myths of origin and the idea of Turanism are instrumentalized in contemporary political discourse in Hungary. More specifically, the article examines how Turanist narratives interact with other memory discourses in Hungary, and what the functions of the political myth of Turanism are in the Hungarian government’s discourse. The study engages with the theoretical background and conceptual framework of politics of memory and political myth, and it aims to contribute to the general analysis of the emergence of political myths and their functions in politics.